2013
DOI: 10.1051/ijmqe/2013044
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy measurement in building: A litterature review, application on an energy efficiency research demonstrated building

Abstract: Abstract. Measuring the energy efficiency of buildings and its confrontation with the current Building Energy Simulations now faces knowledge of what is commonly called "occupancy". This work has been made in order to implement a monitoring system on a research demonstrator building at DLRCA in Angers (France). The goals were first to know the occupancy as input data of models but also to build occupancy models. Occupancy can be defined as all the action of occupants that affect building energy efficiency. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Some authors, such as Chen et al [35] suggested as a possible solution the crowdsourcing technique which requires that each occupant signs the presence in the analyzed area. Other authors, instead, suggested placing near the door a computer with a simple software where the occupants can note when they enter or leave the room [36] . PIR sensors are low cost and easy to deploy but present several drawbacks: If occupants are static, it is possible a wrong detection because they are limited to movement [37] ; cold or warm air flows can be interpreted as motions determining false positives [38] .…”
Section: Measurementsmentioning
confidence: 99%
“…Some authors, such as Chen et al [35] suggested as a possible solution the crowdsourcing technique which requires that each occupant signs the presence in the analyzed area. Other authors, instead, suggested placing near the door a computer with a simple software where the occupants can note when they enter or leave the room [36] . PIR sensors are low cost and easy to deploy but present several drawbacks: If occupants are static, it is possible a wrong detection because they are limited to movement [37] ; cold or warm air flows can be interpreted as motions determining false positives [38] .…”
Section: Measurementsmentioning
confidence: 99%
“…An important challenge for improving the energy performance is the impact of occupancy behavior [4]. Occupancy behavior here refers to all actions of occupants (including presence) that affect building energy consumption [2]. Occupancy behavior affects both individual equipment in buildings and building-wide infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…Most commercial outlets are mandated by government laws to provide accurate estimates of occupant counts in real-time. Lastly, occupant presence is the major driving factor for energy consumption in buildings (Chang and Hong 2013;Caucheteux et al 2013). Consequently, several approaches for simulating, monitoring and optimizing energy consumption in buildings including the model based approaches have become prominent and have received significant research attention (Arendt et al 2016).…”
Section: Introductionmentioning
confidence: 99%